Microcellular graphene foam for improved broadband electromagnetic interference shielding. (June 2016) - Shen, Bin; Li, Yang; Yi, Da; Zhai, Wentao; Wei, Xingchang; Zheng, Wenge
Abstract: As reported, the foaming of layered graphene films into porous graphene foams could improve their performance for absorbents, catalysis and supercapacitors. Herein, to emphasize the impact of porous structure on electromagnetic interference (EMI) shielding, the direct comparison between graphene film (G-film) and corresponding microcellular graphene foam (G-foam) in terms of EMI shielding efficiency has been investigated in a broadband frequency range of 8.2–59.6 GHz, including X-band, Ku-band, K-band, Ka-band, and U-band. Consequently, despite the lower electrical conductivity of the as-prepared G-foam, it exhibited an improved average shielding effectiveness (SE) of ∼26.3 dB over the entire frequency range in comparison with that of G-film (∼20.1 dB). Implication of the results suggested that the foaming of layered graphene films into porous graphene foams could lead to an improvement in EMI shielding, which should be ascribed to the formation of improved internal multiple reflections at the large cell–matrix interfaces owing to the existence of microcellular structure in G-foam. We believe that this research would open up new opportunity for the development of graphene foams in the field of EMI shielding.